Application of Information and Communication Technology in Traditional Medicine and Healing Knowledge Management: Stakeholders’ Perspectives from Tanzania - Iwata, John Jackson (University of Dar es Salaam Library Journal, 2024)
This study examined the application of information and communication technology (ICT) in managing traditional medicine across four districts of Njombe, Masasi, Singida, and Magu, and the Institute of Traditional Medicine in Dar es Salaam, Tanzania. Specifically, the study examined how Tanzanian stakeholders use ICT to manage traditional medicine and healing knowledge, how they use ICT, how it affects the ecosystem of traditional medicine and healing knowledge, how ready they are to adopt ICT applications, and what obstacles they face when integrating ICT. Using a mixed-methods approach and informed by the Technology Acceptance Model and the Information System Success Model, the study deployed a questionnaire survey, semi-structured interviews, focus group discussions, and observations to collect data from a sample of 71 respondents comprising traditional healers, prospective users, researchers, and district coordinators. The resultant data were subjected to thematic and descriptive statistical analyses facilitated by the Statistical Package for Service Solutions. The study found severely limited use of modern technologies, such as computers, in managing traditional medicine and healing knowledge. Although stakeholders owned smartphones, their use was constrained by financial limitations, inadequate ICT skills, and insufficient technological infrastructure. Despite these challenges, participants in this study acknowledged the importance of using ICT in managing traditional medicine and healing knowledge and that they were ready to use it. However, ICT was not fully utilised in managing such knowledge in Tanzania, hence enhancing ICT infrastructure, implementing targeted training programmes for stakeholders, and establishing clear-cut policies and guidelines for ICT use in managing traditional knowledge. Keywords: Indigenous knowledge, Information and Communication Technology, Knowledge management, Traditional healers, Traditional medicine, Healing knowledge. https://dx.doi.org/10.4314/udslj.v19i2.3